Development of a STEM-Project Model to Enhancing Science Process Skills High School Physics Subject - Raharjo, Semiono; Puspita, Yenda (Proceeding International Conference on Religion, Science and Education, 2024)
The background to this research is the low level of science process skills due to a lack of them students are accustomed to carrying out experimental or practical activities in physics learning in previous classes or levels. The aim of this research is to develop a STEM-Project model to determine the level of understanding of science process skills in high school physics subjects that is feasible, effective and practical. This research is development research (Research and Development) using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The research instruments used were validation sheets, interviews and questionnaires. Product trials were carried out at SMA Negeri 1 Piyungan in class XI for the 2023/2024 academic year. The results of the research can be concluded: (1) The average results of the feasibility test assessment of material aspects have a validity of 91% with a very valid category with (very good) and the LKPD aspect with a validity of 93% is very valid (2) The average results of the module readability assessment are 80.67% in the very well read category. (3) The average result of student response assessment to the module is 80% in the very good category. (4) The average result of teacher response assessment to the module is 93% in the very good category. This means that the Project-STEM model can have a significant and effective effect on improving understanding of science process skills in physics subjects at SMA Negeri 1 Piyungan.